PENDIDIKAN KARAKTER BERBASIS GERAKAN LITERASI DI SEKOLAH DASAR - Sri Subiyanti; Murtono Murtono; Suad Suad (Universitas Muria Kudus, 2020)
The purpose of this study was to develop and test the effectiveness of the character education module based on the school literacy movement. This type of research uses Research and Development (RnD). The research subjects used were fifth grade elementary school students in the RA Kartini Cluster, Jaken District, Pati Regency. Data collection techniques by means of observation, interviews, documentation, and questionnaires. The data was collected using observation sheets, interview sheets, photos of activities, and filling out questionnaires. Sources of data obtained from filling out questionnaires, observations, and responses from school principals, class teachers, subject teachers, students, and school committees on the implementation of the module. The resulting module is validated by material experts and module experts. Small group trials were conducted in fifth grade SDN Mojoluhur, Jaken District, Pati Regency. Meanwhile, product use trials were carried out in fifth grade SDNs in the RA Kartini Cluster, Jaken District, Pati Regency. Data analysis techniques are data collection, data presentation, and drawing conclusions and using the t-test to determine the effectiveness of the module. The questionnaire instrument test used validity and reliability, while the quality of the module in the study used expert validation. The results showed: (1) a character education module developed based on the school literacy movement for elementary schools; (2) the character education module based on the school literacy movement is declared valid, the percentage of eligibility criteria for the validator is 75% (feasible) and 83% (very feasible); (3) the character education module based on the school literacy movement is effective for instilling character education in elementary school students. This is shown in the t test the effectiveness of -121.696 1.86 was obtained and the average student character questionnaire before and after using the module increased by 30.08%; (4) the results of teacher responses from observations showed 75.6% (good).